Cardiac Rehabilitation - Maiorana, A.; Neubeck, L.; Williams, Sian; Hill, Keith (Oxford University Press, 2017)
Building upon its predecessor's reputation as the definitive resource on the subject, this new edition of the Oxford Textbook of Geriatric Medicine offers a comprehensive and multinational examination of the field.